Selenium Effect Threshold for Soil Nematodes Under Rice Biofortification - Song, Jiaping; Liu, Xiaodong; Wang, Zhangmin; Zhang, Zezhou; Chen, Qingqing; Lin, Zhi-Qing; Yuan, Linxi; Yin, Xuebin (Frontiers in Plant Science, 2022)
Crop biofortification with inorganic selenium (Se) fertilizer is a feasible strategy to improve the health of residents in Se-deficient areas. For eco-friendly crop Se biofortification, a comprehensive understanding of the effects of Se on crop and soil nematodes is vital. In this study, a rice pot experiment was carried out to test how selenite supply (untreated control, 5, 10, 15, 20, 25, 30, 35, 40, 45, 50, 100, or 200 mg Se kg-1) in soil affected rice growth, rice Se accumulation, and soil nematode abundance and composition. The results showed that selenite supply (5~200 mg kg-1) generally increased the number of rice tillers, rice yield and Se concentrations in rice grains. In soil under 10 mg kg-1 Se treatment, the genus composition of nematodes changed significantly compared with that in the control soil. With increased Se level (> 10 mg kg-1), soil nematode abundance decreased significantly. Correlation analysis also demonstrated the positive relationships between soil Se concentrations (total Se and bioavailable Se) with rice plant parameters (number of rice tillers, rice yield, and grain Se concentration) and negative relationships between soil Se concentrations (total Se and bioavailable Se) with soil nematode indexes (nematode abundance and relative abundance of Tobrilus). This study provides insight into balancing Se biofortification of rice and soil nematode community protection, and suggests the effective concentrations for total Se (1.45 mg kg-1) and bioavailable Se (0.21 mg kg-1) to soil nematode abundances at 20% (EC20) level as soil Se thresholds. At Se concentrations below these thresholds, rice plant growth and Se accumulation in the grain will still be promoted but the disturbance of the soil nematodes would be negligible.